Physical and mechanical properties of wood of plantation grown Albizia lebbeck in the savannah ecological zone, Ghana - Enoch Gbapenuo Tampori; Francis Kofi Bih; Kwaku Antwi; Issah Chakurah (Les, 2024)
The increasing scarcity of major commercial tropical hardwood species has necessitated the utilization of plantation grown exotic timber species as a potential means of maintaining Ghana's foundation of timber resources. To better consider Albizia lebbeck as a substitute for wood species which are being seriously over-exploited to the point of commercial extinction, its wood properties were characterized to expatiate its utilization potentials. Three mature plantation grown Albizia lebbeck trees with diameters 45-50 cm at breast height were purposively selected and sampled at four stem height levels of tree height. The samples were sawn into the required sizes in accordance with the British standard, BS 373 (1957) for testing. The heartwood and sapwood proportions were evaluated and the samples were examined for hardness, bending strength (MOE and MOR), compression strength parallel to grain, shear strength parallel to grain, and air-dry density. All trees had a significantly higher heartwood than sapwood percentage. The air-dry density values at 12% MC were 868 kg/m3, 806 kg/m3, 695 kg/m3 and 564 kg/m3 for four sections of the stem (heights 0-25%, 26-50%, 51-75% and 76-100%). In general, the plantation grown Albizia lebbeck exhibited favourable strength values, suggesting that it is endowed with adequate properties for being an alternative species to supply the wood industry.